Motor cortex stimulation in refractory pelvic and perineal pain: Report of two successful cases12. Issue 1 (5th June 2012) - Louppe, Jean‐Marie; Nguyen, Jean‐Paul; Robert, Roger; Buffenoir, Kevin; de Chauvigny, Edwige; Riant, Thibault; Péréon, Yann; Labat, Jean‐Jacques; Nizard, Julien
Abstract Aims In some patients, with refractory chronic pelvic and perineal pain, pain and quality of life are barely alleviated despite optimal medical treatment, infiltrations and surgical release of the pudendal nerve. The management of these patients is complex, especially after failure of neuromodulation techniques (spinal cord stimulation. S3 nerve root stimulation and direct stimulation of the pudendal nerve). We report the first two cases illustrating the value of motor cortex stimulation (MCS), in this new indication. Methods The history, decision‐making process, intraoperative findings and results of this technique are presented. The perineal cortical area was identified by intraoperative motor evoked potentials in the external anal sphincter, confirming its location in the primary motor cortex between the inferior and superior limb positions. As predictive value of repetitive transcranial magnetic stimulation (rTMS) in the identification of responders to MCS for pain is now established, we performed pre‐operative rTMS sessions for both patients. Results The first patient was a 74‐years‐old woman who reported an 11‐year history of left lateral perineal pain. The second patient was a 45‐year‐old woman who reported a 4‐year history of perineal pain following hysterectomy with ovariectomy. After respectively 40 months and 19 months of follow up, both patients reported an improvement of pain ranging from 40 to 50%. Time to onset of pain on sitting was markedly improved from a few minutes to 90 minutes, and largely contributing to improvement of activities of daily living and of quality of life. Conclusion These two first cases suggest that motor cortex stimulation constitutes a new treatment for refractory pelvic and perineal pain, and should be considered after failure of conventional neuromodulation techniques, especially spinal cord stimulation. Neurourol. Urodynam. 32: 53–57, 2013. © 2012 Wiley Periodicals, Inc.